Diabetes impairs the vascular effects of aldosterone mediated by G protein-coupled estrogen receptor activation - Ferreira, Nathanne S.; Cau, Stêfany B. A.; Silva, Marcondes A. B.; Manzato, Carla P.; Mestriner, Fabíola L. A. C.; Matsumoto, Takayuki; Carneiro, Fernando S.; Tostes, Rita C. (Frontiers in Pharmacology, 2015)
Aldosterone promotes non-genomic effects in endothelial and vascular smooth muscle cells via activation of mineralocorticoid receptors (MR) and G protein-coupled estrogen receptors (GPER). GPER activation is associated with beneficial/protective effects in the vasculature. Considering that vascular dysfunction plays a major role in diabetes-associated complications, we hypothesized that the beneficial effects mediated by vascular GPER activation, in response to aldosterone, are decreased in diabetes. Mesenteric resistance arteries from female, 14-16 weeks-old, control and diabetic (db/db) mice were used. Phenylephrine (PhE)-induced contractions were greater in arteries from db/db vs. control mice. Aldosterone (10 nM) increased maximal contractile responses to PhE in arteries from control mice, an effect elicited via activation of GPER. Although aldosterone did not increase PhE responses in arteries from db/db mice, blockade of GPER and MR decreased PhE-induced contractile responses in db/db mesenteric arteries. Aldosterone also reduced the potency of acetylcholine (ACh)-induced relaxation in arteries from both control and db/db mice via MR-dependent mechanisms. GPER antagonism further decreased ACh-induced relaxation in the control group, but did not affect ACh responses in the diabetic group. Aldosterone increased extracellular signal-regulated kinase (ERK)1/2 phosphorylation in arteries from control and db/db mice by a GPER-dependent mechanism. GPER, but not MR, gene and protein expression, determined by RT-PCR and immunoblotting/immunofluorescence assays respectively, were increased in arteries from db/db mice vs. control arteries. These findings indicate that aldosterone activates both vascular MR and GPER and that the beneficial effects of GPER activation are decreased in arteries from diabetic animals. Our results further elucidate the mechanisms by which aldosterone influences vascular function and contributes to vascular dysfunction in diabetes.